Simulating the passive confinement of rectangular concrete prisms allowing for size effect. Issue 7 (30th July 2022) - Hao, Xinkai; Visintin, Phillip; Oehlers, Deric J.
Abstract : Tests have shown that providing passive confinement to concrete, either through the use of internal stirrups, external fibre-reinforced polymer (FRP) wraps, FRP tubes or steel tubes, can increase the concrete strength and, in particular, the concrete ductility, thereby allowing greater absorption of energy and consequently ductile failure. The problem of including the benefits of passive confinement in design is in generalising the effect of passive confinement because it varies with the member size, the configuration of the confining reinforcement and material properties. In this paper, all aspects of the complex fundamental mechanics of passive concrete confinement are explained both qualitatively and quantitatively through the use of shear–friction and bond–slip mechanics. The mechanics model was found to have a good correlation with test results. An analysis-oriented procedure is described for quantifying the passive stress–strain of concrete for rectangular sections and it is envisaged that this can be used to develop simplified rules for design, in particular for new types of members and those with new materials.